Thermostimulated sol-gel transition in suspensions of sulfate zirconium oxychloride - Chiavacci, L. A.; Santilli, Celso Valentim [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Craievich, A. F. (Munksgaard Int Publ Ltd, 1997)
The sol-gel transition of an aqueous solution of zirconium oxychloride modified by sulfuric acid (Zr:S 3:1) has been studied by small-angle X-ray scattering (SAXS) performed in situ during one cycle of heating and cooling between 298 and 358 K. The experimental SAXS curves exhibit three regions, at small, medium and high q values, characteristic of the Guinier, 'fractal' and Pored regimes, respectively. The value of 5.5 Angstrom for the radii of the primary particles, obtained from the cross over of the Pored and fractal regimes, is consistent with the size of the inner core of the polynuclear Zr18O4(OH)(38.8)(SO4)(12.6).33H(2)O molecule. These molecules aggregate as small clusters (31 Angstrom) of fractal structure, with a dimensionality D = 2.16 in the sol. The value of the fractal dimensionality, which is characteristic of ideal branched polymers, decreases during heating, attaining a value of 2.0, characteristic of swollen polymers. Above the critical temperature (329 K), the average size of aggregates increases abruptly to 200 Angstrom and the fractal dimensionality decreases to D = 1.75, this value being characteristic of a cluster-cluster aggregation process.